Zachowania konsumpcyjne kobiet i wpływ reklamy na ich decyzje nabywcze - Zięba, Alicja (My University, 2015)
Praca składa się z trzech teoretycznych rozdziałów i czwartego badawczego. W pierwszym rozdziale przedstawiono teoretyczną wiedzę na temat zachowań konsumentów na rynku. W drugim przeanalizowano główne aspekty decyzji nabywczych konsumentów oraz zobrazowano proces podejmowania decyzji zakupowych. Trzeci rozdział zawiera merytoryczne aspekty marketingu skierowanego do kobiet oraz analizę reklamy jako głównego narzędzia reklamowego. Dzięki wiedzy zawartej w rozdziałach merytorycznych możemy w sposób teoretyczny poznać meritum zachowań konsumpcyjnych kobiet. Rozdział empiryczny stanowi próbę odpowiedzi na główne pytanie badawcze, mianowicie: jaki jest wpływ reklamy na decyzje nabywcze kobiet?. W pracy zastosowano ankietę jako metodę badawczą. Badania przeprowadzono w grupie stu kobiet z powiatu gorlickiego w wieku 30 – 40 lat. Celem pracy magisterskiej jest próba odpowiedzi na pytanie: Jaki wpływ na decyzje nabywcze kobiet wywiera główne narzędzie promocji, jakim jest reklama. Za cele pośrednie przyjęłam poznanie stopnia znajomości mechanizmów rynkowych wśród kobiet, określenie determinantów ich działań rynkowych oraz zbadanie metod podejmowania przez konsumentki decyzji zakupowych.

The title of thesis is „Consuming behaviour of women and the influence of an advertisement for their purchasing decisions”. The thesis consists of three theoretical chapters and the fourth research one. The first chapter presents theoretical knowledge of consumers’ behaviour in the market. In the second chapter the main aspects of purchasing decisions of consumers have been analysed as well as the process of making buying decisions has been illustrated. The third chapter includes the essential aspects of marketing directed to women and the analysis of an advertisement as a main advertising tool. Due to the knowledge included in the essential chapters we can find in a theoretical way the essence of consuming behaviour of women. The empirical chapter is an attempt to answer the main research question, that is: What is the influence of an advertisement for purchasing decisions of women?. In the thesis a questionnaire has been used as a research method. The research was conducted in the group of one hundred women at the age of 30-40 from the Gorlice county. The aim of this thesis is an attempt to answer the question: What is the influence of an advertisement as a main promotion tool for purchasing decisions of women? For indirect aims I have taken finding the degree of knowledge of market mechanisms among women, establishing determinants of their market activities as well as studying the methods of making buying decisions by consumers.
Consuming behaviour of women and the influence of an advertisement for their purchasing decisions
Keywords: reklama; konsumentka; rynek; marketing; decyzja; zachowanie; produkt; usługa; advertisement; consumer; market; marketing; decision; behaviour; product; service